A novel in situ diffusion strategy to fabricate high performance cathodes for low temperature proton-conducting solid oxide fuel cells. Issue 22 (23rd May 2018) - Hou, Jie; Miao, Lina; Hui, Jianing; Bi, Lei; Liu, Wei; Irvine, John T. S.
Abstract : A novel in situ Pr diffusion strategy based on a Sm0.2 Ce0.8 O2− δ –Pr(Pr0.5 Ba1.5 )Cu3 O7− δ (3 : 7 wt%) compound is developed to achieve a perovskite-related proton-blocking composite cathode Ce1− x Pr x O2− δ –Ba2 CeCu3 O7.4 –Sm2 Ba1.33 Ce0.67 Cu3 O9 –CuO for BaZr0.1 Ce0.7 Y0.2 O3− δ -based proton-conducting SOFCs. Abstract : Developing new low-cost high-performance cobalt-free cathode materials for low temperature proton-conducting solid oxide fuel cells (H-SOFCs) has been an imperative topic. In response to this challenge, we herein develop a novel in situ Pr diffusion strategy based on a Sm0.2 Ce0.8 O2− δ –Pr(Pr0.5 Ba1.5 )Cu3 O7− δ (SDC–PBCu, 3 : 7 wt%) compound, to achieve a perovskite-related proton-blocking composite cathode (PBCC) Ce1− x Pr x O2− δ –Ba2 CeCu3 O7.4 –Sm2 Ba1.33 Ce0.67 Cu3 O9 –CuO (PDC–BCC–SBCC–CuO) for BaZr0.1 Ce0.7 Y0.2 O3− δ -based H-SOFCs. The single cell achieves a remarkable performance with a maximum power density (MPD) of 1000 and 566 mW cm −2, corresponding to the interfacial polarization resistance ( R P ) of 0.037 and 0.188 Ω cm 2 at 700 and 600 °C, respectively. The XRD results demonstrate that the PBCu phase disappears after the calcination of the mixed SDC–PBCu composite powder at 900 °C, with the formation of four new phases including fluorite structured PDC, orthorhombic layered material BCC, tetragonal perovskite-related SBCC and a small quantity of metallic oxide CuO, being favorable for a superior cathode performance. The ascendant electrochemical performance including the very high MPD and the lower R P obtained here indicate that the quaternary cobalt-free PBCC PDC–BCC–SBCC–CuO is a preferable alternative for high-performance low-temperature H-SOFCs.